A comparative study of the decision-making procedures of managers in national government agencies - Samillano, Clarivic
Decison-making is one othe most recurring responsibilities facing a manager in any organization. The way in which a manager approach this task reflects his decision style. Oftentimes, managers are unaware of how they go about making decision. For some unknown reason, decison making is seldom subjected to careful scrutiny that poor decisions are among on of its consequence. It is on this theme that this study was founded. Entitled " A Comparative study of the Decision Making Styles of Junior and Senior Educational Managers," it is an attempt to compare the decision-making styles between junior and senior educational manager vis a vis the factors of age, educational attainment and work experience- in the government and in their respective position. It also aims to know if there exists relationship between all these factors and the decision styles derived. In the following discussion, the researchers endeavored to evaluate the decision styles practiced by the educational managers, specifically the head of schools and principals of the District of Iloilo City and Oton